ANALISIS PENGARUH KEPUASAN TERHADAP LOYALITAS ANGGOTA PADA UNIT SIMPAN PINJAM KOPERASI PRAJA NIRMALA (KPN) KABUPATEN KETAPANG - Ridha Anggiashandra; Samsuddin Samsuddin; Neni Triana Maswardi (Jurnal Produktivitas: Jurnal Fakultas Ekonomi Universitas Muhammadiyah Pontianak, 2018)
The purpose of this study was to determine the effect of satisfaction on loyalty of Members of the Savings and Loans Unit of the Praja Nirmala Cooperative, Ketapang Regency. This study uses quantitative methods, the sample used in this study is as many as 77 people with a sampling technique in the form of purposive sampling, which is borrowing a minimum of five months and has become a member of at least two years. The conclusion of this study used data analysis, namely: validity test, reliability test, normality test, simple linear regression analysis, correlation coefficient (R), coefficient of determination (R2), and model feasibility tests, using the help of SPSS 24 application. The result of the linear regression equation is Y = 0.299 + 0.915 X. For the results of the correlation coefficient (R) explains that the correlation value is 0.728 which means that the satisfaction and loyalty of members has a strong enough relationship, while the value of the coefficient of determination (R2) is 0.530 which means the influence satisfaction with the loyalty of members using the services of the Nirmala Praja Cooperative is 53% while the remaining 47% is influenced by other variables not examined in this study.